Analisis Strategi Representasi Diri dan Personal Branding pada Beauty Content Creator di Instagram Reels - Rifayani, Tsanaara Qinthara; Harahap, Junardi (Aceh Anthropological Journal, 2025)
The rise of short-form video platforms, specifically Instagram Reels, has transformed social media into a crucial, highly strategic stage for individuals to perform and negotiate their identities. This study critically analyzes the self-representation and personal branding strategies employed by Fani Rahmawati, a beauty content creator, on Instagram Reels to build a public image that is both credible and emotionally relatable. Utilizing a descriptive qualitative approach and virtual ethnography, the research delves into the subtle symbolic, social, and performative dynamics inherent in digital identity construction. Data collection relied on participative observation of Fani's Reels content (March–April 2024) and in-depth interviews with the creator, her videographer, and an active follower. Trustworthiness was ensured through source triangulation and member-checking. Thematic analysis, informed by Goffman's impression management and Jones and Pittman's strategic self-presentation, revealed five interconnected themes: visual consistency, an intimate communication style, constructed authenticity, emotional audience engagement, and the significant role of the production team. The findings indicate that Fani successfully fosters a "friendly older sister" persona by deliberately mixing aesthetic consistency, the use of informal, engaging language (ingratiation), and the calculated disclosure of personal narratives to establish high credibility. This branding process is shown to be less about individual spontaneity and more about a collective practice negotiated among the creator, her team, and the platform’s algorithmic demands. This research contributes to digital anthropology and media studies by arguing that personal branding on visual short-video platforms is a complex social performance rooted in strategic impression management, the cultivation of parasocial relationships, and crucial production collaboration. Abstrak: Meningkatnya popularitas platform video pendek, khususnya Instagram Reels, telah menjadikan media sosial sebagai panggung strategis yang penting bagi individu untuk menampilkan dan menegosiasikan identitas mereka. Penelitian ini menganalisis secara kritis strategi representasi diri dan personal branding yang dijalankan oleh Fani Rahmawati, seorang beauty content creator, di Instagram Reels guna membentuk citra publik yang kredibel dan memiliki kedekatan emosional. Menggunakan pendekatan kualitatif deskriptif dan etnografi virtual, penelitian ini menggali dinamika simbolik, sosial, dan performatif yang tersirat dalam konstruksi identitas digital. Data dikumpulkan melalui observasi partisipatif terhadap konten Reels Fani (Maret–April 2024) dan wawancara mendalam dengan tiga informan kunci: kreator, videografer, dan pengikut aktif. Keabsahan data dijamin melalui triangulasi sumber dan member-checking. Analisis tematik, yang berlandaskan pada kerangka impression management Goffman dan strategic self-presentation Jones dan Pittman, mengidentifikasi lima tema utama yang saling terkait: konsistensi visual, gaya komunikasi akrab, autentisitas terkonstruksi, keterlibatan emosional audiens, serta peran signifikan tim produksi. Hasil penelitian menunjukkan bahwa kesuksesan Fani dalam membangun persona "kakak bersahaja" bersumber dari perpaduan strategis antara konsistensi estetika, penggunaan bahasa informal yang menarik (ingratiation), dan pengungkapan narasi personal yang diperhitungkan untuk menciptakan kredibilitas tinggi. Proses branding ini membuktikan bahwa ia bukan sekadar spontanitas individu, melainkan praktik kolektif yang dinegosiasikan antara kreator, timnya, dan tuntutan algoritmik platform. Studi ini berkontribusi pada kajian antropologi digital dan studi media dengan menegaskan bahwa personal branding di platform video pendek visual merupakan performa sosial yang kompleks, didorong oleh manajemen kesan strategis, pembentukan hubungan parasosial, serta kolaborasi produksi yang krusial.